2023
DOI: 10.1590/1980-220x-reeusp-2022-0364en
|View full text |Cite
|
Sign up to set email alerts
|

Hospital sustainability indicators and reduction of socio-environmental impacts: a scoping review

Abstract: Objective: To synthesize knowledge about hospital sustainability indicators and evidence of reduced socio-environmental impact. Method: Literature scoping review using Pubmed, Science Direct, Scielo and Lilacs databases. Studies in a time frame of 10 years, addressing hospital sustainability indicators and evidence of reduced socio-environmental impact published in any language were included. Results: A total of 28 articles were included, most were applied research, published in 2012, in English. Studies sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
(156 reference statements)
0
0
0
Order By: Relevance
“…In this sense, Chart 1 presents reflective questions that induce good sustainable practices in the nursing process. Developed based on scientific evidence ( 33 - 35 ) , these prospective questions aim to contribute to the responsible and sustainable use of resources in health services.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, Chart 1 presents reflective questions that induce good sustainable practices in the nursing process. Developed based on scientific evidence ( 33 - 35 ) , these prospective questions aim to contribute to the responsible and sustainable use of resources in health services.…”
Section: Methodsmentioning
confidence: 99%
“…A recently carried out study analyzed environmentally sustainable actions in the medication process, from receipt from the pharmacy to the disposal of waste by nursing professionals. The study identified a 74.8% reduction in chemical, infectious and sharps waste and a 48% reduction in waste sent to landfill, after educational nursing interventions ( 33 ) . These data reveal that the nursing process needs to intuit critical-reflective reasoning through systematic continuing education activities with the involvement of all actors.…”
Section: Methodsmentioning
confidence: 99%